2003
DOI: 10.5897/ajb2003.000-1030
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase Production by Aspergillus flavus Linn Isolate NSPR 101 fermented in sawdust, bagasse and corncob

Abstract: Bagasse, corncob and sawdust were used as lignocellulosic substrates for the production of cellulase enzyme using Aspergillus flavus after ballmilling and pretreatment with caustic soda. From the fermentation studies, sawdust gave the best result with an enzyme activity value of 0.0743IU/ml while bagasse and corncob gave 0.0573IU/ml and 0.0502IU/ml respectively. The three lignocellulosics gave their maximum enzyme activities at about the twelfth hour of cultivation, suggesting that the 12th hour is the optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 11 publications
1
48
1
4
Order By: Relevance
“…Our results are comparable to Ojumu et al [23] who reported high cellulase activity from 3% pretreated saw dust, bagasse and corn cob as substrate respectively. Substrate concentration is a dynamic influencing feature that affects the yield and initial hydrolysis rate of cellulose [24].…”
Section: Production Of Cellulasesupporting
confidence: 80%
“…Our results are comparable to Ojumu et al [23] who reported high cellulase activity from 3% pretreated saw dust, bagasse and corn cob as substrate respectively. Substrate concentration is a dynamic influencing feature that affects the yield and initial hydrolysis rate of cellulose [24].…”
Section: Production Of Cellulasesupporting
confidence: 80%
“…Cellulose is the major component of plant biomass and the major biopolymer found in abundance on earth, and much of the cellulose exists as wastes. Such wastes include straw, corn cobs, wood wastes, peat, bagasse and waste paper [3]. In principle, all lignocellulosics can be converted into simple sugars which can serve as useful raw materials in the production of fuel, animal feedstock and feedstock for chemical synthesis [4].…”
Section: öZetmentioning
confidence: 99%
“…A. flavus BS1 competently utilized different lignocellulosic substrates and supported higher levels of cellulase activity [61]. A. flavus Linn NSPR 101 showed the production of cellulase on various natural substrates like bagasse, corncob and sawdust [62]. Thus, production of cellulase may vary between species of fungi; and from the above studies, it is evident that the wide range and higher enzyme activities are possible on waste lignocellulosic biomass as substrate.…”
Section: Solid-state Fermentationmentioning
confidence: 97%